Magia y realidad en la literatura de la revolución cubana - Martín Sastre, María Jesús (Verba hispanica, 2013)
There is no innocent literature. Literature is made by love, by hate, by a woman, by an idea, by an injustice, by a hope, to praise or to criticize, but I think literature has never been isolated, pure, detached. ... Literature cannot escape life and history (Manuel Cofino Lopez, 1985: 9697). Cofino Lopezs own literature is no exception. The clear contrast that he presents in The Last Woman and the upcoming battle between magic and reality, ignorance and culture, past and present has a purpose. The author raises the need to end with the old beliefs in order to progress.This inextricable link between magic and reality of the Revolution is present in several novels of the Cuban Revolution. It shows how the two interact, as well as how past and present intermingle. Moreover, we find that magic is present throughout, and is fully compatible with the Revolution. This does not make it erroneous to believe in the stories of Magic Realism. It is a mistake on the part of the revolution and those who write about it for attempting to deny people the magic of their superstitions and beliefs, since magic is not the enemy of progress. They are part of their lives and their culture, and are something that should be respected.
Keywords: Cofino López, Manuel, 1936-1987; kubanska književnost; 20st.; magični realizem; revolucija